Imbalanced ownership transformation and land use within an urban area: a case study of Beijing. (May 2018) - Li, Jiaming; Li, Yuheng; Zhang, Wenzhong; Yu, Jianhui
Highlights: The results confirm 2003 as the turning point, after which market power weakened in China's reform. We used kernel density estimation to investigate spatial pattern of different ownership economies and its change in Beijing. State-owned sector was located significantly closer to central government than private sector in Beijing. Contrary to popular belief, historical reasons were not decisive to SOE's location. Rootedness and immobility of collective economy have been underlined. More importantly, rootedness may led to the recession of rural economy in the interior of China after 1990s. Abstract: Governments and scholars fail to agree on whether marketization has been promoted continuously in China, and it remains a controversial issue in China's gradual reform. To understand China's reform process, micro firm data from Beijing has been employed to investigate the changing shares in different ownership economies and their spatial pattern within the city. The findings are as follows. First, 2003 was a turning point in the process of China's reform, after which market power weakened. Second, the state-owned enterprise (SOE) sector is significantly closer to the central government than the private sector in Beijing. Contrary to popular belief, historical reasons were not decisive in determining the SOE location. Finally, immobility has made the collective economy unique and it even led to the recession of rural economies in China's interior after the1990s.